Serventuário das trevas, Os Bolcheviques da Impressa Católica (Fortaleza/CE, 1922-1932). - Pinto, José Aloísio Martins (2005)
The research, using the newspaper O NORDESTE, an organ founded in June 1922, under the auspices of the Archdiocese of Fortaleza, analyzes the censorship imposed on the Bolsheviks from 1922 to 1932. In addition to anti-communism, the organ was in favor of other practices. developed by the Catholic Traditionalism of the time. [...]